Control of vector populations using genetically modified mosquitoes - Wilke, André Barreto Bruno; Gomes, Almério de Castro; Natal, Delsio; Marrelli, Mauro Toledo (Revista de Saúde Pública, 2009)
The ineffectiveness of current strategies for chemical control of mosquito vectors raises the need for developing novel approaches. Thus, we carried out a literature review of strategies for genetic control of mosquito populations based on the sterile insect technique. One of these strategies consists of releasing radiation-sterilized males into the population; another, of integrating a dominant lethal gene under the control of a specific promoter into immature females. Advantages of these approaches over other biological and chemical control strategies include: highly species-specific, environmentally safety, low production cost, and high efficacy. The use of this genetic modification technique will constitute an important tool for integrated vector management.